Legal battles: transgender inmates’ rights - Redcay, Alex (The prison journal, 2020)
Challenging binary gender norms and common conceptions of the differences between sexes, transgender individuals are misunderstood, feared, and often subjected to stigma. As a result, transgender individuals are exposed to harassment, violence, and employment discrimination. The negative outcomes of this exposure include poverty, unemployment, trauma, homelessness, arrest, and/or incarceration. Within the correctional system, stigmatization is heightened, leading to grave consequences for transgender inmates. The goal of this article is to highlight these outcomes, as illustrated from legal case histories, and to suggest best practice recommendations for correctional system improvements in ensuring the rights of transgender inmates.